Snowbound with the Amish bachelor [large type] - Johns, Patricia (Romance writer) (Johns, Patricia. Redemption's Amish Legacies., 2021)
"For social worker Grace Schweitzer, arriving at Ben Hochsteller's farm to pick up an abandoned baby feels like stepping into her past - especially after a blizzard forces her to stay . . . She's losing her heart to ben and the faith she once held dear, but has she changed too much to return to this life?" -- Back cover.